Judgment method for floating charge performance of lithium cobalt oxide material
Through scanning electron microscope and polarization microscope combined with TOF-SIMS technology, the problem of cobalt tetroxide determination in lithium cobalt oxide materials was solved, and the accurate evaluation of the floating charging performance of lithium cobalt oxide materials was achieved and the battery stability was improved, simplified the measurement process and improved the measurement process. Environmentally friendly.
Patent Information
- Application Number
- CN202310786952.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2024-12-31
AI Technical Summary
The prior art cannot accurately determine the existence form and content of residual cobalt tetroxide in lithium cobalt oxide materials, which affects the floating charging performance and stability of the battery, and the measurement method is complex and not environmentally friendly.
Scanning electron microscopy and polarization microscopy combined with TOF-SIMS technology are used to accurately visualize and quantify the presence form and content of cobalt tetroxide through image processing and elemental analysis to judge the floating charge performance of lithium cobalt oxide materials and the stability at high voltage.
The accurate evaluation of the floating charging performance of lithium cobalt oxide material can be effectively judged, the existence form and content of cobalt tetroxide can be improved, the stability and safety of the battery at high voltages are simplified, and the measurement process is environmentally friendly and efficient.
Smart Images

Figure CN119223952A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a method for determining the floating charge performance of a lithium cobalt oxide material. Background Art
[0002] Lithium cobalt oxide material is made of cobalt tetroxide and lithium carbonate as raw materials, and is formed by high-temperature roasting. There is a small amount of cobalt tetroxide residue. The residual cobalt tetroxide will have an adverse effect on the electrochemical performance of the battery, especially the floating charge performance. At the same time, the doping effect will also affect the cobalt tetroxide residue, so the cobalt tetroxide residue not only reflects the degree of lithiation, but also indirectly reflects the doping effect. Accurately measuring the content of residual cobalt tetroxide in lithium cobalt oxide material is an important indicator for quantitatively evaluating the degree of lithium cobalt oxide reaction. The commonly used method in the prior art is to use the different redox reaction abilities of lithium cobalt oxide and cobalt tetroxide in acidic solution. By selecting a suitable acidic solution and dissolution time, lithium cobalt oxide is dissolved, while cobalt tetroxide is not dissolved. The undissolved cobalt tetroxide is collected and the Co element content is tested by ICP to quantify the cobalt tetroxide. This method is complicated and not environmentally friendly, and it is impossible to know the existence form of cobalt tetroxide and the doping situation at the defect position. Summary of the invention
[0003] The present application provides a method for judging the floating charge performance of a lithium cobalt oxide material, which can visualize the existence form of cobalt tetroxide in the lithium cobalt oxide material and quantify its content through image processing to judge the stability of the lithium cobalt oxide material under high voltage. The present application also combines polarizing microscopy and TOF-SIMS to judge the floating charge failure risk of the lithium cobalt oxide material, and can achieve a comprehensive evaluation of the floating charge performance of the lithium cobalt oxide material.
[0004] In a first aspect, the present application provides a method for judging the floating charge performance of a lithium cobalt oxide material, wherein the floating charge performance includes the stability of the lithium cobalt oxide material under high voltage, and the method comprises the following steps: S100: mixing the lithium cobalt oxide material and a binder and coating the mixture on a current collector to obtain a pole piece, cutting the pole piece to obtain a pole piece with a cross section of the lithium cobalt oxide material exposed, S200: performing scanning electron microscope backscattered electron scanning imaging on the pole piece with a cross section of the lithium cobalt oxide material described in step S100 to obtain a spliced scanning electron microscope image, S300: selecting the spliced scanning electron microscope image described in step S200 to obtain a statistical area, and obtaining the cobalt oxide content in the statistical area, and S400: determining the stability of the lithium cobalt oxide material under high voltage according to the cobalt oxide content described in step S300.
[0005] In some embodiments, the step S100 includes: mixing the lithium cobalt oxide material and the binder, coating the mixture on a single side of the current collector, and drying the mixture to obtain the electrode. The drying may be natural drying, drying in an oven, or other conventional drying methods in the prior art, which may be selected according to actual conditions and are not limited in this application.
[0006] The pole piece includes a current collector and an active material layer, the active material layer contains the lithium cobalt oxide material, the current collector includes a positive electrode current collector, and the present application has no particular restrictions on the positive electrode current collector, as long as the purpose of the present application can be achieved, for example, it can include aluminum foil or aluminum alloy foil, and the present application has no particular restrictions on the thickness of the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5μm to 12μm.
[0007] The binder is selected from at least one of polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), and polytetrafluoroethylene (PTFE). Preferably, the binder is polyvinylidene fluoride.
[0008] In some embodiments, the mass ratio of the lithium cobalt oxide material to the binder is 8 to 9.5:1, and the coating (active material layer, hereinafter the same) thickness of the pole piece is 80 to 150 μm. Preferably, the mass ratio of the lithium cobalt oxide material to the binder is 9:1. If the coating thickness of the pole piece is too thin, for example, less than 80 μm, it is not conducive to statistics, resulting in reduced accuracy of the results, that is, a coating with a suitable thickness range is more conducive to statistics and calculation of results.
[0009] Exemplarily, the coating thickness of the pole piece is 80 μm, 90 μm, 100 μm, 120 μm, 130 μm, 150 μm or a range consisting of any two of the above values.
[0010] In some embodiments, in step S200, the voltage during the backscattered electron scanning imaging of the scanning electron microscope is 2 to 5 kV, and the magnification is 800 to 2000X. Wherein, the magnification: M = L / I, L is the size of the cathode ray tube, and I is the distance between two adjacent points during raster scanning. M is performed by adjusting the current of the scanning coil. The smaller the current, the smaller the deflection angle of the electron beam, and the larger the magnification. The magnification is not the larger the better. It should be selected according to the effective magnification and the need to analyze the sample, and maintain a certain relationship with the resolution. The magnification in the above range is preferred. More preferably, the voltage during the backscattered electron scanning imaging of the scanning electron microscope is 2 kV, and the magnification is 1000X.
[0011] Exemplarily, in step S200, the voltage during the backscattered electron scanning imaging process of the scanning electron microscope is 23 kV, 4 kV, 5 kV, or a range consisting of any two of the above values.
[0012] Exemplarily, in step S200, the magnification in the backscattered electron scanning imaging process of the scanning electron microscope is 800X, 1000X, 1200X, 1400X, 1500X, 1600X, 1800X, 2000X or a range consisting of any two of the above values.
[0013] In some embodiments, in step S300, the area of the statistical region is recorded as M, satisfying: M ≥ 1000*80 μm 2 The appropriate coating thickness, the appropriate proportion of active materials, and the appropriate range of statistical area work together to improve the test accuracy.
[0014] In some embodiments, in step S300, obtaining the cobalt oxide content in the statistical region includes: obtaining the cobalt oxide area and the lithium cobaltate area in the statistical region, and obtaining the cobalt oxide content according to the cobalt oxide area and the lithium cobaltate area.
[0015] In some embodiments, before obtaining the cobalt tetroxide area and the lithium cobalt oxide area in the statistical area, the method also includes: using a BSE image to identify the cobalt tetroxide and the lithium cobalt oxide in the statistical area and calibrating the grayscale sequence to obtain grayscale distribution thresholds of cobalt tetroxide and lithium cobalt oxide, respectively, and using the grayscale distribution thresholds of cobalt tetroxide and lithium cobalt oxide to respectively divide the cobalt tetroxide and lithium cobalt oxide in the statistical area.
[0016] In some embodiments, the grayscale distribution threshold of the cobalt oxide is 135 to 255, and the grayscale distribution threshold of the lithium cobalt oxide is 79 to 123. The upper and lower limits of the thresholds are used to ensure that the complete Co3O4 / lithium cobalt oxide particle outlines are demarcated.
[0017] In some embodiments, obtaining the cobalt tetroxide content according to the cobalt tetroxide area and the lithium cobaltate area includes: recording the cobalt tetroxide area as A, recording the lithium cobaltate area as B, and the cobalt tetroxide content is calculated according to Formula I, cobalt tetroxide content = [A / (A+B)]*100% Formula I.
[0018] In some embodiments, in step S400, determining the stability of the lithium cobalt oxide material under high voltage according to the cobalt oxide content includes: when the cobalt oxide content is higher than a threshold value, determining that the lithium cobalt oxide material has poor stability under high voltage. When the cobalt oxide content is not higher than a threshold value, determining that the lithium cobalt oxide material has good stability under high voltage. The threshold value ranges from 0.5 to 1%. Preferably, the threshold value is 0.5%.
[0019] Exemplarily, the threshold is 0.5%, 0.6%, 0.8%, 0.9%, 1%, or a range consisting of any two of the above values.
[0020] In some embodiments, the floating charge performance also includes the floating charge failure risk. In step S400, after determining the stability of the lithium cobalt oxide material under high voltage according to the cobalt oxide content, it also includes: using a polarizing microscope to capture images of N randomly selected lithium cobalt oxide particles containing cobalt oxide in the lithium cobalt oxide material at the grain boundaries, and using TOF-SIMS to identify the element types at the grain boundaries of the corresponding N lithium cobalt oxide particles containing cobalt oxide. The floating charge failure risk of the lithium cobalt oxide material is determined according to the number of cobalt-rich element particles at the grain boundaries of the lithium cobalt oxide particles and the type of doping elements, where N≥5.
[0021] In some embodiments, the float charge failure risk of the lithium cobalt oxide material is determined based on the number of cobalt-rich particles at the grain boundaries of the lithium cobalt oxide particles, including: if the number of cobalt-rich particles at the grain boundaries of the lithium cobalt oxide particles is greater than N / 2, then the float charge failure risk is determined to be high. Wherein, the cobalt-rich particles mainly include cobalt tetroxide particles, and the distribution position of Co3O4 is outside the particles or exists alone, then the float charge failure risk is low. If Co3O4 is distributed at the grain boundary, then the float charge failure risk is high. This is because LiCoO2 particles will crack under high voltage, and it is more likely to occur at the grain boundary. If cracking occurs, it will further induce electrolyte side reactions, and Li + As the transmission path becomes longer, the electron / ion conductivity of the battery cell gradually declines, resulting in performance deterioration.
[0022] In some embodiments, the risk of floating charge failure of lithium cobalt oxide materials is determined according to the types of doping elements at the grain boundaries of lithium cobalt oxide particles, including: if the types of doping elements at the grain boundaries of lithium cobalt oxide particles are ≥ 2, then the risk of floating charge failure is determined to be high. Mg element doping has the characteristics of improving electronic conductivity, capacity retention, and phase change reversibility, Al element doping has the characteristics of phase change reversibility and capacity retention, and Ti element doping has the characteristics of improving capacity, capacity retention, and rate improvement. Doping elements can play a good role in inhibiting phase change. If the types of doping elements at the Co3O4 position are more, the doping elements in the LiCoO2 bulk phase will be reduced accordingly, and the structural stability will decrease.
[0023] In some embodiments, the determination of the floating charge performance of the lithium cobalt oxide material comprises the following steps: step (1) determining the cobalt oxide content in multiple batches of lithium cobalt oxide materials, and recording the batch of lithium cobalt oxide materials in which the cobalt oxide content is not higher than a threshold as lithium cobalt oxide material one; step (2) using a polarizing microscope to capture the number of cobalt-rich element particles at the grain boundaries of N randomly selected lithium cobalt oxide particles containing cobalt oxide in the lithium cobalt oxide material one in step (1), and recording the batch in which the number of cobalt-rich element particles at the grain boundaries is less than or equal to N / 2 as lithium cobalt oxide material two; step (3) using TOF-SIMS to identify the types of doping elements at the grain boundaries of N lithium cobalt oxide particles containing cobalt oxide in the lithium cobalt oxide material two in step (2), and counting the number of lithium cobalt oxide particles with the type of doping elements at the grain boundaries greater than or equal to 2 in multiple batches in turn, and recording it as K. The smaller the K value, the better the floating charge performance of the corresponding batch of lithium cobalt oxide materials. In the above judgment process, judging the content of cobalt tetroxide is more important than judging the number of cobalt-rich element particles at the grain boundaries, and judging the number of cobalt-rich element particles at the grain boundaries is more important than judging the types of impurity elements at the grain boundaries. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0025] Figure 1 This is a spliced scanning electron microscope image of Example 1 of the present application;
[0026] Figure 2 for Figure 1 Threshold image of cobalt tetroxide in the medium;
[0027] Figure 3 for Figure 2 The operation interface image when the threshold is divided;
[0028] Figure 4 for Figure 1 Threshold segmentation image of lithium cobalt oxide;
[0029] Figure 5 for Figure 4 The operation interface image when the threshold is divided;
[0030] Figure 6 This is an image of one of the grains in the LiCoO2 particle under a polarizing microscope;
[0031] Figure 7 This is an image of another grain in the LiCoO2 particle under a polarizing microscope;
[0032] Figure 8 This is an image taken when the Raman microscope objective lens is adjusted to about 1000X magnification;
[0033] Fig. 9 This is the Raman test spectrum of the brighter part inside the LiCoO2 particle;
[0034] Fig.10 This is the Raman test spectrum of Co3O4 standard substance;
[0035] Fig.11 This is the Raman test spectrum of LiCoO2;
[0036] Fig.12 This is a curve diagram of battery expansion rate testing of Examples 1 to 5 of the present application. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0038] Embodiment design:
[0039] Example 1
[0040] Preparation of positive electrode
[0041] Aluminum foil is used as the positive electrode current collector, and a layer of lithium cobalt oxide slurry (positive electrode active material layer) is uniformly coated on the surface of the aluminum foil. The lithium cobalt oxide slurry includes LiCoO2 (positive electrode active material) of batch 1 and polyvinylidene fluoride (binder). The mass ratio of LiCoO2 (LCO) of batch 1 to the polyvinylidene fluoride (PVDF) is 9:1. The coating thickness of the lithium cobalt oxide slurry is 85 μm. The positive electrode active material layer is cut by an ion cutting device (such as JEOL IB-09010CP) to expose the cross section of the positive electrode active material.
[0042] In Examples 2 to 5, different from Example 1, Examples 2 to 5 use LiCoO2 from batches 2 to 5 in sequence, that is, only the batches of lithium cobalt oxide materials are different in Examples 1 to 5, and the different batches may be lithium cobalt oxide materials from different batches of the same manufacturer or from different batches of lithium cobalt oxide materials from different manufacturers.
[0043] Test Method
[0044] (1) Determination of cobalt tetroxide content
[0045] Take multiple backscattered scanning electron microscope images at 1000X and 2KV (FEI Apreo S can be used), then stitch them seamlessly. After stitching, select 1000×80um 2 In the BSE-SEM mode, Co3O4 is brighter, LiCoO2 is darker, and the pores are the darkest. Figure 1 , use threshold division to select appropriate thresholds to separate Co3O4 (135~255) and LiCoO2 (79~123), see Figures 2 to 5 , and the area A of Co3O4 and the area B of LiCoO2 are counted respectively. The average content of cobalt tetroxide in the three groups of parallel tests of Examples 1 to 5 is calculated by the formula: cobalt tetroxide content = [A / (A+B)]*100%. See Table 1 for details.
[0046] Table 1
[0047] Sample No. first Second time The third time average Example 1 (Batch 1) 1.50% 1.72% 1.66% 1.63% Example 2 (Batch 2) 1.40% 1.55% 1.42% 1.46% Example 3 (Batch 3) 0.35% 0.53% 0.45% 0.44% Example 4 (Batch 4) 0.36% 0.50% 0.44% 0.43% Example 5 (Batch 5) 0.38% 0.50% 0.46% 0.45%
[0048] As can be seen from Table 1, the mean content of cobalt oxide in batches 1 to 2 is higher than the threshold value (the threshold value range is 0.5 to 1%), which can determine that batches 1 and 2 have poor stability under high voltage, and the mean content of cobalt oxide in batches 3 to 5 is lower than the threshold value, which can determine that batches 3 to 5 have good stability under high voltage. That is, batches 3 to 5 are recorded as lithium cobalt oxide material one.
[0049] (2) Determination of the number of cobalt-rich particles at grain boundaries
[0050] Polarized light microscopy was used to capture images of grain boundaries of five randomly selected lithium cobalt oxide particles from batches 3 to 5 of lithium cobalt oxide materials. Figures 6-7 , Figure 6 and Figure 7 It is the same LiCoO2 particle. It can be seen that the LiCoO2 particle contains two grains. Figure 6 The dark color is a grain. Figure 7 The bright color is a grain, for example, Figure 7 In the figure, the left part is dark and the right part is light. It can be seen that Co3O4 exists at the grain boundary of the two grains and the edge of the particles. The number of Co3O4 existing at the grain boundary of the two grains in 5 lithium cobalt oxide particles was counted. The specific statistical method can refer to the conventional means of the prior art, which will not be described in detail in this application. After statistics, it was found that the number of cobalt-rich particles at the grain boundaries in batches 3 to 5 was less than 2, that is, batches 3 to 5 were recorded as lithium cobalt oxide material two.
[0051] (3) Determination of impurity types at grain boundaries
[0052] Combined with the images of the grain boundaries of the 5 lithium cobalt oxide particles captured by the polarizing microscope in the previous step, TOF-SIMS is used to identify the element types at the grain boundaries of the 5 lithium cobalt oxide particles corresponding to batches 3 to 5 in turn, and the number of lithium cobalt oxide particles with more than or equal to 2 impurity elements at the grain boundaries in the corresponding batches is counted, respectively, and recorded as K. The specific statistical method can refer to the conventional means of the prior art, and this application is not described in detail here. After statistics, the K of batch 5 is 0, and the K of batches 3 to 4 are all greater than 0. It can be seen that the floating charge performance of the lithium cobalt oxide material of batch 5 is the best.
[0053] verify
[0054] (1) Confirmation of Co3O4 location
[0055] Figure 1 The brighter part in the image was confirmed as Co3O4 by Raman characterization. Specifically, the scanning electron microscope mosaic was first obtained, the characteristic area of Co3O4 was circled, and then the Raman microscope objective was adjusted to about 1000X, the circled (boxed) characteristic position was found, and the spectrum was collected using a 532nm laser. Figure 8 The bright spherical particles are the added Co3O4 standard (Co3O4 and LiCoO2 are mixed in a mass ratio of 1:1 to make slices), and the irregular particles are LiCoO2. The bright area inside the LiCoO2 particles is confirmed by Raman to be the location of Co3O4, see the test spectrum Figures 9-11 And Table 2, Fig. 9 This is the Raman test spectrum of the brighter part inside the LiCoO2 particle. Fig.10 This is the Raman test spectrum of Co3O4 standard substance. Fig.11 This is the Raman test spectrum of LiCoO2. It can be seen that the Raman spectrum of the bright part of LiCoO2 contains both the characteristic peaks of LiCoO2 and the characteristic peaks of Co3O4, which proves that the bright part is Co3O4.
[0056] Table 2
[0057]
[0058] (2) Battery expansion rate test
[0059] a) Test temperature is 45℃; b) Rest 4H; c) 0.4C CC to 4.45V, CV to 60mA; d) 4.45V CVto 1440H&100mA; e) THK measurement frequency: Initial, first stage floating charge 1950H measured every 96H.
[0060] Combination Fig.12 , Fig.12From left to right at the intersection of THK swelling (thickness expansion rate) 20% are Example 1 (batch 1), Example 2 (batch 2), Example 3 (batch 3), Example 4 (batch 4), and Example 5 (batch 5). It can be seen that Batch 5 has the best floating performance, which is consistent with the above test results of this application.
[0061] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for determining the floating charge performance of a lithium cobalt oxide material, characterized in that: The floating charge performance includes the stability of the lithium cobalt oxide material under high voltage, and the judging method includes the following steps: S100: mixing a lithium cobalt oxide material and a binder and applying the mixture on a current collector to obtain a pole piece, and cutting the pole piece to obtain a pole piece with a cross section of the lithium cobalt oxide material exposed; S200: performing scanning electron microscope backscattered electron scanning imaging on the pole piece exposed in the cross section of the lithium cobalt oxide material described in step S100 to obtain a spliced scanning electron microscope image; S300: Frame the spliced scanning electron microscope image in step S200 to obtain a statistical region, and obtain the cobalt tetroxide content in the statistical region; S400: Determine the stability of the lithium cobalt oxide material under high voltage according to the cobalt oxide content described in step S300.
2. The determination method according to claim 1, characterized in that: The step S100 includes: mixing the lithium cobalt oxide material and the binder, coating the mixture on a single side of the current collector, and drying the mixture to obtain the electrode.
3. The determination method according to claim 2, characterized in that: The mass ratio of the lithium cobalt oxide material to the binder is 8 to 9.5:1; The coating thickness of the pole piece is 80-150 μm.
4. The determination method according to claim 1, characterized in that: In step S200, the voltage during the backscattered electron scanning imaging process of the scanning electron microscope is 2 to 5 kV; The magnification is 800~2000X.
5. The determination method according to claim 1, characterized in that: In step S300, the area of the statistical region is recorded as M, which satisfies: M ≥ 1000*80 μm 2 .
6. The determination method according to claim 1, characterized in that: In step S300, obtaining the cobalt tetroxide content in the statistical area includes: Using the backscattered image to identify cobalt tetroxide and lithium cobaltate in the statistical area and calibrate the grayscale sequence, respectively obtaining grayscale distribution thresholds of cobalt tetroxide and lithium cobaltate, wherein the grayscale distribution threshold of cobalt tetroxide is 135-255, and the grayscale distribution threshold of lithium cobaltate is 79-123; Using the grayscale distribution thresholds of cobalt tetroxide and lithium cobalt oxide, respectively, cobalt tetroxide and lithium cobalt oxide are divided out of the statistical area; The cobalt oxide area and the lithium cobalt oxide area in the statistical area are obtained, and the cobalt oxide content is obtained according to the cobalt oxide area and the lithium cobalt oxide area.
7. The determination method according to claim 6, characterized in that: The cobalt oxide content obtained according to the cobalt oxide area and the lithium cobalt oxide area includes: The area of the cobalt oxide is recorded as A, the area of the lithium cobaltate is recorded as B, and the cobalt oxide content is calculated according to formula I; Cobaltous oxide content = [A / (A+B)]*100% Formula I.
8. The determination method according to claim 1, characterized in that: In step S400, determining the stability of the lithium cobalt oxide material under high voltage according to the cobalt oxide content includes: When the cobalt oxide content is higher than a threshold value, it is determined that the lithium cobalt oxide material has poor stability under high voltage; When the cobalt oxide content is not higher than the threshold value, it is determined that the lithium cobalt oxide material has good stability under high voltage; The threshold value ranges from 0.5 to 1%.
9. The determination method according to claim 8, characterized in that: The float charging performance also includes the risk of float charging failure; In step S400, after determining the stability of the lithium cobalt oxide material under high voltage according to the cobalt oxide content, the method further includes: Use a polarizing microscope to capture images of N randomly selected grain boundaries of lithium cobalt oxide particles containing cobalt tetroxide in the lithium cobalt oxide material; Using TOF-SIMS to identify the element types at the grain boundaries of N lithium cobalt oxide particles containing cobalt tetroxide; Determine the float charge failure risk of lithium cobalt oxide materials based on the number of cobalt-rich particles at the grain boundaries of lithium cobalt oxide particles and the types of doping elements; Among them, N≥5; The risk of float charge failure of lithium cobalt oxide materials is determined based on the number of cobalt-rich particles at the grain boundaries of lithium cobalt oxide particles and the type of doping elements, including: If the number of cobalt-rich particles at the grain boundaries of lithium cobalt oxide particles is greater than N / 2, it is determined that the risk of float charge failure is high; If there are ≥2 types of doping elements at the grain boundaries of lithium cobalt oxide particles, the risk of floating charge failure is determined to be high.
10. The determination method according to claim 9, characterized in that: The determination of the floating charge performance of the lithium cobalt oxide material comprises the following steps: Step (1) determining the cobalt oxide content in multiple batches of lithium cobalt oxide materials, and recording the batch of lithium cobalt oxide materials having a cobalt oxide content not higher than a threshold as lithium cobalt oxide material 1; Step (2) The lithium cobalt oxide material 1 in step (1) is sequentially captured using a polarizing microscope to measure the number of cobalt-rich particles at the grain boundaries of N randomly selected lithium cobalt oxide particles containing cobalt trioxide, and the batch with the number of cobalt-rich particles at the grain boundaries being less than or equal to N / 2 is recorded as lithium cobalt oxide material 2; Step (3) The lithium cobalt oxide material 2 in step (2) uses TOF-SIMS to identify the types of doping elements at the grain boundaries of N lithium cobalt oxide particles containing cobalt tetroxide, and counts the number of lithium cobalt oxide particles with the type of doping elements at the grain boundaries being greater than or equal to 2 in multiple batches, recorded as K. The smaller the K value, the better the floating charge performance of the corresponding batch of lithium cobalt oxide materials.